Faktor Yang Mempengaruhi Green Purchase Intention: Dimediasi Oleh Green Trust - Vebriyanto, Sigit; Hadi, Effed Darta (Universitas Islam Kadiri, 2023)
This study aims to investigate the determinants affecting the intention to purchase electric cars in Indonesia, with a specific focus on the Java and Sumatra regions. Electric vehicles represent a promising solution to address environmental concerns, notably the issue of global warming, primarily attributed to emissions from conventional vehicles. Recent data indicates a substantial surge in electric car sales within Indonesia. The research findings indicate that green perceived value has a direct and significant positive impact on the intention to buy electric vehicles. Furthermore, individuals' attitudes and green trust products directly contribute to the intention to purchase electric vehicles. Additionally, green trust serves as an intermediary in reinforcing the positive relationship between green perceived value and green attitudes towards green purchase intention. Conversely, subjective norms did not demonstrate a positive influence on the intention to purchase electric vehicles. These results shed light on the factors that shape consumers' intentions to buy electric vehicles and the extent of their impact, particularly in the regions of Java and Sumatra.